Strengthening Legal Certainty Through the Updating of Village Land Data to Support Land Registration - Handayani, Sri Wahyu; Destyarini, Normalita; Herlan, Asep Ridwan Purbalingga (AIWADTHU: Jurnal Pengabdian Hukum, 2026)
Introduction: This community service activity is motivated by the condition of land data in Pekuncen Village, Banyumas Regency, Central Java Province, which is obsolete both physically and substantively. This condition has resulted in disorderly village land administration that has led to legal cases involving village officials. Such disorder is caused by limitations in human resources in mastering appropriate technology.Purposes of The Devotion: The purpose of this community service is to provide appropriate technology transfer for updating village land data in order to achieve orderly village land administration and legal certainty.Method of The Devotion: The methods used include socialization, mentoring, and monitoring and evaluation of activity outcomes to support sustainability.Results Main Findings of the Devotion: The results of this community service demonstrate a significant impact on improving the capacity of village officials’ human resources through a series of activities that serve as solutions to the identified problems, namely: 1) enhanced understanding of village officials regarding valid documents as the basis for the history of land ownership; 2) improved mastery of computerized administration of juridical land data to ensure greater accuracy and effectiveness in addressing physical document issues of the Letter C Book, which is no longer feasible and contains many torn or missing pages; and 3) improved capacity in managing the administration of juridical land data renewal.